2011
DOI: 10.1097/wno.0b013e3182236427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Brinzolamide on Infantile Nystagmus Syndrome Waveforms: Eyedrops for Nystagmus

Abstract: Background: Recent advances in infantile nystagmus syndrome (INS) surgery have uncovered the therapeutic importance of proprioception. In this report, we test the hypothesis that the topical carbonic anhydrase inhibitor (CAI) brinzolamide (Azopt) has beneficial effects on measures of nystagmus foveation quality in a subject with INS. Methods: Eye movement data were taken, using a highspeed digital video recording system, before and after 3 days of the application of topical brinzolamide 3 times daily in each e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 33 publications
0
10
0
3
Order By: Relevance
“…appears to be based on intersubject comparisons. In rebuttal, Dell'Osso 1 cites an impressive list of 12 papers in support of intrasubject improvement in VA, [5][6][7][8][9][10][11][12][13][14][15][16] but in our view, his interpretation exaggerates any such support. Close inspection reveals that only one of these papers actually provides statistical evidence of such a change, 15 as measured using standard letter charts.…”
Section: Within-subject Measurements Of Vamentioning
confidence: 82%
See 1 more Smart Citation
“…appears to be based on intersubject comparisons. In rebuttal, Dell'Osso 1 cites an impressive list of 12 papers in support of intrasubject improvement in VA, [5][6][7][8][9][10][11][12][13][14][15][16] but in our view, his interpretation exaggerates any such support. Close inspection reveals that only one of these papers actually provides statistical evidence of such a change, 15 as measured using standard letter charts.…”
Section: Within-subject Measurements Of Vamentioning
confidence: 82%
“…6,8,9,11,13,16 In fact, four of these studies only used one subject: Dell'Osso himself. 6,9,11,16 Two of the papers cited were reviews, and thus contained no new data, 10,12 while the remaining three found statistically significant changes in nystagmus waveform characteristics, but failed to detect significant changes in VA. 5,7,14 In three of these studies, 6,9,11 VA was not even measured, but instead NAFX was used as an outcome measure, from which VA was predicted. NAFX is a computed number based on waveform shape and does not include any perceptual component.…”
Section: Within-subject Measurements Of Vamentioning
confidence: 99%
“…Current therapies may improve the INS oscillation but the nystagmus persists. Recently, carbonic anhydrase inhibitors (CAIs), oral Diamox and topical Azopt have shown beneficial therapeutic effects on INS in single subject case reports 5 6. CAI's effects on INS were simulated in a behavioural ocular motor system model and the results suggest that the oral drug may have acted via a peripheral mechanism through the drug's membrane-associated carbonic anhydrase activity within eye muscle enthesial nerve endings 7…”
Section: Introductionmentioning
confidence: 99%
“…The Introduction cited papers showing a strong intersubject correlation between nystagmus waveform foveation quality and VA, but failed to report (not even in the papers that were cited 3,4 ) that these and other published studies demonstrating how therapies that improved the foveation quality in specific INS patients (i.e., intrasubject) also improved their NAFX/VA. [5][6][7][8][9] The increase in peak NAFX value is directly proportional to the VA increase in each patient.…”
mentioning
confidence: 99%
“…The statement is also contradicted by the many patients exhibiting improvement (including 14 of 15 with INS plus albinism 20 ), not only in peak VA but more importantly in the huge increases in VA at gaze angles lateral to that peak. 4,9 The final paragraph contains several misstatements of fact or unsubstantiated conclusions. For the reasons given above, the first conclusion is unjustified and is contradicted by published data.…”
mentioning
confidence: 99%